A review of the prospects for vaccination in African trypanosomiasis. Part II - Murray, M.; Barry, J.D.; Morrison, W. Ivan; Williams, R.O.; Hirumi, H.; Rovis, L.A. (1980)
In part I of this review of the prospects of vaccination against African trypanosomiasis, contained in the previous issue of World Animal Review, the constraints in developing a vaccine were discussed and current knowledge on the molecular biology of the trypanosome and on antigenic variation with respect to possible future vaccines was evaluated. In this part other possible regimes for immunological intervention, including the immunogenicity and cross reactivity of trypanosome subcellular fractions, reduction of host susceptibility to African trypanosomes by the non-specific use of immunostimulants or chemotherapy and also the role of trypanotolerant livestock in such approaches are discussed.